Contribution Financing Possible in the “Demographically Stressed” Pension System - Ernst Niemeier (Wirtschaftsdienst)
Abstract Despite the aging demographic in Germany, retirement pensions are enough to finance pensioners’ living expenses. The increase of the real income will exceed the burden of the increasing number of older people so that people of working age can bear the higher pension payments. Pensions that have been restrained due to political mistakes should be reimbursed out of taxes. General social programmes have to be financed by taxes, too.